2022
DOI: 10.1080/10872981.2022.2054304
|View full text |Cite
|
Sign up to set email alerts
|

The virtual interview format for fellowship recruitment in obstetrics and gynecology: a nationwide survey of program directors

Abstract: Due to Covid-19, fellowship programs could not conduct in-person interviews during the 2020–2021 interview cycle and were forced to implement virtual interviews. We conducted two nationwide surveys of residency and fellowship Program Directors (PDs) involved in the Obstetrics and Gynecology (Ob/Gyn) Subspecialty Fellowship match cycle to gain a better understanding of virtual interviews from each of their perspectives. 1) Fellowship PDs’ confidence in using a virtual platform to holistically evaluate applicant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Most of the candidates preferred VIs with an option of an in-person site visit or a hybrid model. Similarly, the PDs seem to believe that the VI has a role in the future, either exclusively or via a hybrid model, even in instances in which they believed the process limited them from fully expressing their program’s potential ( 5 , 6 , 11 , 13 , 14 ). Our study found that 61% of PCCM PDs would like to conduct VIs in the future, even under usual circumstances.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the candidates preferred VIs with an option of an in-person site visit or a hybrid model. Similarly, the PDs seem to believe that the VI has a role in the future, either exclusively or via a hybrid model, even in instances in which they believed the process limited them from fully expressing their program’s potential ( 5 , 6 , 11 , 13 , 14 ). Our study found that 61% of PCCM PDs would like to conduct VIs in the future, even under usual circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…The data from the NRMP specialties matching service PD survey with particular attention to the PCCM PDs responses were used ( 12 ). The preliminary survey questionnaire was inspired by the survey research conducted by Ponterio and colleagues ( 5 ). The preliminary survey questionnaire was reviewed by M.B.F., who has extensive experience in medical education.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ponterio et al surveyed obstetrics and gynecology program directors finding that, although all responders agreed that there was a financial benefit in virtual interviewing for applicants, they also expressed concern about truly judging applicants' interest in their program. 19 On a more encouraging note, if virtual interviews continue, it may allow program directors to see a more diverse pool of applicants, a goal the broad field of cardiology and the American College of Cardiology have emphasized remains a glaring deficit that needs to be addressed. 20 , 21 Flexibility in interview scheduling may also limit interview cancellations especially owing to often unpredictable travel delays.…”
Section: Discussionmentioning
confidence: 99%
“…Scoring. To avoid neutral responses to questions and increase variability in responses (Ponterio et al, 2022;Weems & Onwuegbuzie, 2001), a 4-point Likert scale, ranging from "never like this" to "always like this," was used to rate the items. Negatively worded items were scored 1 for "never like this," 2 for "sometimes like this," 3 for "most of the time like this," and 4 for "always like this."…”
Section: Scale Development and Expert Reviewmentioning
confidence: 99%